THE CONSTRAINTS IN PERFORMING SIGHT TRANSLATION: A BRIEF DISCUSSION ON THE PROBLEMS OF TRANSLATING ENGLISH WRITTEN TEXTS INTO INDONESIAN ORAL TEXTS - Adventina Putranti (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Oral translation, commonly called interpreting, is a verbal communication activity involving two parties speaking different languages, assisted by an interpreter. One mode of interpreting is simultaneous interpreting in which an interpreter delivers a source language (SL) message into a target language (TL) message simultaneously as the speaker’s statement proceeds (Nolan 3). One specific kind of simultaneous interpreting is sight translation. It is a form interpreting a written SL message into a spoken TL message (Ginori&Scimone 18). Although the SL message is written, this does not lessen the constraints of doing this job because the simultaneousness of this activity still demands the interpreters’ ability in working using two languages at the same time, as well as having the skills required for an interpreter. What is meant by constraints is performance constraints (Pochhacker 19) as the result of time limitation, the demand for the interpreter’s promptness and the accuracy of message transferred.This paper intends to observe the constraints in performing sight translation. For that purpose, this paper is going to explain the constraints experienced by interpreters when they are carrying out sight translation tasks. Since Interpreting class is available as a subject given at the English Letters Department, Sanata Dharma University, the data were obtained from the students of an Interpreting class who were assigned to perform sight translation. To limit the scope of discussion, the sight translation observed has been focused on the oral translation of English written texts into Indonesian spoken interpretation.